La lucha por la libertad - Scarrow, Simon (Scarrow, Simon. Gladiator., 2012)
After Marcus Cornelius Primus's father is murdered and his mother kidnapped and enslaved, Marcus is forced to fight as a gladiator, enduring brutal training while he secretly plots to avenge his father's death and rescue his mother.